Colegio público para secundaria de cobertura zonal en la comuna 12 de ibagué, Tolima (2023)
This project is focused on solving the deficit of public educational places for elementary and middle school in commune 12 of Ibagué. Currently, the student population of children between 11 and 16 years old is 4,425 and the existing school infrastructure only has the capacity to serve 46%, that is, there is coverage for 2,052 students and there is a deficit of 2,373 places. So, through an architectural project, the aim is to increase the coverage of secondary education places in commune 12 so that the student population is not forced to go to neighboring communes to study.